Chaperone-Usher Pili Loci of Colonization Factor-Negative Human Enterotoxigenic Escherichia Coli - (:unkn) unknown (FRONTIERS MEDIA SA, 2017)
Enterotoxigenic Escherichia coli (ETEC) is one of the most common causes of diarrhea worldwide. Among the 25 different ETEC adhesins, 22 are known as "colonization factors" (CFs), of which 17 are assembled by the chaperone-usher (CU) mechanism. Currently, there is no preventive therapy against ETEC, and CFs have been proposed as components for vaccine development. However, studies of diarrhea-causing ETEC strains worldwide indicate that between 15 and 50% of these are negative for known CFs, hindering the selection of the most widespread structures and suggesting that unknown adhesins remain to be identified. Here, we report the result of a comprehensive analysis of 35 draft genomes of ETEC strains which do not carry known adhesin genes; our goal was to find new CU pili loci. The phylogenetic profiles and serogroups of these strains were highly diverse, a majority of which produced only the heat-labile toxin. We identified 10 pili loci belonging to CU families beta (1 locus), gamma(2) (7 loci), kappa (1 locus), and pi (1 locus), all of which contained the required number of open reading frames (ORFs) to encode functional structures. Three loci were variants of previously-known clusters, three had been only-partially described, and four are novel loci. Intra-loci genetic variability identified would allow the synthesis of up to 14 different structures. Clusters of putative gamma(2)-CU pili were most common (23 strains), followed by putative beta-CU pili (12 strains), which have not yet been fully characterized. Overall, our findings significantly increase the number of ETEC adhesion genes associated with human infections.